Transition programs for adolescents and young adults with spina bifida: A mixed‐methods systematic review. (22nd November 2020) - Choi, Eun Kyoung; Bae, Eunjeong; Jang, Mina
Abstract: Aims: To identify the components of transition programs for the successful transition of adolescents and young adults with spina bifida and to synthesize the literature findings on the transition outcomes of the programs. Design: Mixed‐methods systematic review. Data sources: PubMed, CINAHL, PsycINFO, and Web of Science (January 2010‐June 2019). Review methods: The methodological quality was appraised using the Mixed Methods Appraisal Tool and Cochrane Risk of Bias Tool. Extracted data were summarized as tables. For data synthesis, a sequential explanatory design was used. Results: Eight studies were selected. The main components of the transition programs identified the participants' characteristics and intervention strategies. Quantitative studies reported only positive transition outcomes, including independence and satisfaction with social support and transition experience, whereas negative outcomes such as negative experiences communicating with providers and uncertainty were further reported in qualitative studies. Conclusion: For development and implementation of a successful transition program, it is necessary to assess the characteristics and needs of the participants and incorporate their needs with input from parents and trained healthcare providers. Impact: When planning transition programs, a comprehensive effort that encompasses program development, implementation, and evaluation, based on developmental tasks and long‐term perspectives, is needed. Transition program that reflect the cultural characteristics of Eastern and developing countries are needed. 摘要: 目的: 确定过渡计划的组成部分, 以成功实现患有脊柱裂的青少年和青壮年的过渡, 并综合有关过渡结果的文献调查结果。 设计: 混合方法系统评估。 数据来源: PubMed、CINAHL、PsycINFO和科学网(2010年1月‐2019年6月)。 评估方法: 采用混合方法评估工具和Cochrane偏倚风险工具对方法学质量进行评估。提取的数据汇总为表格。对于数据综合, 采用顺序说明设计。 结果: 共选择了八项研究。过渡计划的主要组成部分确定了参与者的特征和干预策略。定量研究仅报告了积极的过渡成果, 包括独立性以及对社会支持和过渡经历的满意度, 而定性研究还报告了消极成果, 例如与提供者沟通的负面经历和不确定性。 结论: 对于制定和实施成功的过渡计划而言, 有必要评估参与者的特征和需求, 并将他们的需求与父母和训练有素的医疗服务提供者的意见相结合。 影响: 在编制过渡计划时, 需要基于发展任务和长期观点作出综合努力, 包括计划的制定、实施和评估。需要制定反映东方和发展中国家文化特征的过渡计划。